Toughness enhancement and tribochemistry of the Nb-Ag-N films actuated by solute Ag. (15th September 2017) - Ren, Ping; Zhang, Kan; He, Xin; Du, Suxuan; Yang, Xiaoyang; An, Tao; Wen, Mao; Zheng, Weitao
Abstract: The high-hardness nature of transition metal nitrides (TMN) has been widely exploited for industrial applications ranging from wear-resistance and cutting tools to scratch-resistant films. To design TMN-based films displaying a further improved toughness and a reduced friction represent urgent challenges. Up to now, creating a nanocomposite structure by introducing a very small content of the metal phase has been considered as a common strategy to enhance hardness and toughness. Herein, we present a new approach to incorporate few solute Ag atoms (∼1.5 at.%) into NbN film to form a Nb-Ag-N solid solution structure, achieving enhanced hardness and toughness, coupled with improved wear-resistance ability and remarkable drop in coefficient of friction (CoF). Hardness and toughness enhancement as well as the tribochemistry actuated by solute Ag have been investigated by combined experimental and density functional theory (DFT) analyses. Results show that the hardness enhancement induced by solute Ag stems from the combination of variation in microstructure and increment in bulk modulus B and C44 . DFT calculations and electronic structure analyses further reveal that the presence of hybridizations between Ag 5s, 4d orbitals and N p-electrons is responsible for increment in B and C44 ; furthermore, the appearance of additional Ag eg states contributes to the improved toughness. Additionally, solute Ag can activate self-oxidation by forming Ag2 O + Nb2 O5 at the surface, which is beneficial for the formation of silver niobate (AgNbO3 ) during the sliding, thereby triggering the falling of the CoF at only 1.5 at.% Ag. Incorporation of few solute Ag atoms into TMN may provide a new strategy to improve the comprehensive properties including hardness, toughness, friction and wear-resistance. Graphical abstract: Image 1